Alternatif Pengembangan Ruang Terbuka Hijau yang Sesuai untuk Permukiman Padat (Studi Kasus: Perumahan Dosen IKIP Jatikramat Bekasi) - Ndruru, Fonahia; Rilatupa, James E. D.; Pasaribu, Ramos P. (Universitas Muara Bungo, 2025)
This study aims to formulate alternatives for the development of Green Open Spaces (GOS) in densely populated residential areas in the IKIP Jatikramat Bekasi Lecturers' Housing Complex, with a focus on innovative and adaptive strategies to address land constraints and the ecological and social needs of the area. The research method uses a qualitative approach through literature study and descriptive case analysis. Data was obtained through literature on Green Open Spaces (RTH) and green infrastructure, as well as field observations related to green space potential, drainage conditions, and community participation. The findings were analysed in an integrated manner to formulate relevant recommendations for the development of Green Open Spaces (RTH). The results of the study show that the development of Green Open Spaces (RTH) in dense settlements can be done through the use of vertical and horizontal space. Recommendations include the application of green roofs and green walls, the construction of pocket parks on limited land, and community gardens to strengthen social interaction and food security. Rain gardens and bioretention are considered effective in reducing water runoff, while tree planting and green infrastructure-based drainage revitalisation increase environmental absorption. Successful implementation is determined by community participation, policy support, environmental education, and stakeholder collaboration.